Production, Marketing and Future Prospects of Mandarin in Nepal - Regmi, Anmol; Dhungana, Surya Mani (Journal La Lifesci, 2024)
Citrus reticulata is a vital fruit crop in Nepal, where its demand is very high and has been produced as the main source of income in the hilly region. Nepal offers suitable topography, climate and soil for the profitable production of mandarins with great taste, precocity and high nutritive values. This study attempts to analyze the production trend, export and import, current scenario and prospects of mandarin in Nepal. The study employed a comprehensive review and synthesis of secondary data, including statistical records, publications from relevant organizations, and academic literature from 2001 to 2023, to analyze the production, marketing status, and prospects of mandarin in Nepal. The findings of the study shows that the production of mandarin is in increasing trend with an average annual growth rate of 7.04% from fiscal year 2019/20 to 2020/21 and cultivating area by 33.84 % from fiscal year 2019/20 to 2021/22. The study emphasizes the economic value of mandarins, especially in the mid-hill’s region, as well as their health advantages because of their fiber and antioxidant content. The yield of mandarin has decreased because of several issues, such as high investment costs, lack of adoption of improved technology, poor orchard management, diseases and pests, unstable prices and profit margins along with inappropriate market channels. Therefore, to strengthen this subsector, it is advised to focus on developing mandarin productivity through conventional mechanization, better adoption of technology, price intervention, market recognition, HLB management, establishment of storage and processing centers, and diplomatic relations for easy international marketing.